2021
DOI: 10.2903/sp.efsa.2021.en-6832
|View full text |Cite
|
Sign up to set email alerts
|

2021 EFSA/IZSAM Animal Health Crisis Preparedness Exercise with Mediterranean Countries

Abstract: In July 2021, the European Food Safety Authority (EFSA) jointly devised, developed and delivered an online workshop on animal health crisis preparedness with IZSAM, focusing on Rift Valley fever (RVF). The overall training objective was to improve incident response collaboration between animal and public health authorities from multiple countries, using a ‘One Health’ approach. The 4 specific exercise learning objectives were to test and improve skills in: (a) outbreak investigation; (b) prevention of RVF outb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…This agrees with the finding of Eltayb et al [61], who demonstrated that only half of the farmers in their study had knowledge of zoonotic diseases. Although these diseases are considered exotic in Cyprus, appropriate biosecurity measures should be in place to prevent the occurrence or diminish the consequences of any outbreaks [62].…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with the finding of Eltayb et al [61], who demonstrated that only half of the farmers in their study had knowledge of zoonotic diseases. Although these diseases are considered exotic in Cyprus, appropriate biosecurity measures should be in place to prevent the occurrence or diminish the consequences of any outbreaks [62].…”
Section: Discussionmentioning
confidence: 99%